Effects of Solution Matrix on Moringa oleifera Seeds and Banana Peel in Eliminating Heavy Metals, Fluoride and Turbidity from Synthetic groundwater samples - Ab Aziz, Nur Adila; Jayasuriya, Niranjali; Fan, Linhua; Zakaria, Mohd Azuan; Pakir, Faizal; Daud, Zawawi; Abdulrahman Oyekanmi, Adeleke; Ismail, Norli (International Journal of Integrated Engineering, 2018)
Plant-based biomass has become an environmental-friendly water purification agent in replacing conventional chemicals. In the previous study, Moringa oleifera (MO) seeds and banana peel (BP) have been selected based on their moderate to high effectiveness in removing lead, cadmium, nickel, arsenic, turbidity, and fluoride from synthetic groundwater samples. This study was aimed to investigate further the effects of solution matrix on the biomass effectiveness. Batch experiments were conducted by using coagulation technique and the initial pH of the solutions was controlled to be at pH 7. The results demonstrate that the removal rates for most of the pollutants in multi-contaminant solution were higher compared to the single-contaminant solution. The reason could be due to electrostatic or mutual interactions between contaminants present in the solution thus improved the removal rates of those contaminants. The findings are significantly important to understand the effects and removal behavior of the biomass in different solution matrix.